The Preconditions of Rebirth of Serbian and Croatian Nationalism in the of the XX century - Dirgėla, Mantas (Sociologija. Mintis ir veiksmas, 1998)
Nationalism in one way or the other affected all the political processes in the Yugoslavian territories. The tension between Serbian and Croatian nationalism is of special importance. Therefore the analysis of these nationalisms is central for understanding the political events in the region. The article differentiates a few interrelated preconditions for the understanding of the two nationalisms. These are the history, the economic conditions, social-psychological factors and the interaction between foreign politics and nationalism.